Assessment of clinic-biochemical parameters in severe acute malnutrition children admitted in a tertiary care hospital of Western Uttar Pradesh, India - Akshay Shukla,; Gaurav Arya,; Alok Kumar Gupta,; Kumar, Navin; Santosh Kumar Barman, (Asian Journal of Medical Sciences, 2023)
Background: Severe acute malnutrition (SAM) is one of the major causes of mortality and morbidity among children in developing countries and is an important contributing factor to deaths occurring from preventable causes in children <5 years of age. Decreasing child mortality and improving maternal health depends heavily on reducing malnutrition. Aims and Objectives: To study the prevalence, risk factors, medical complications, and outcome (morbidity and mortality) of children admitted with SAM along with biochemical changes. Materials and Methods: This was an observational cross-sectional study conducted in the Department of Pediatrics, Uttar Pradesh University of Medical Sciences, Saifai, Uttar Pradesh, India. Indoor Patient admitted in the department of pediatrics with SAM between ages 6 and 59 months. A total of 100 children were included in the present study. This study was done from January 2019 to June 2020. Results: Approximately 59% of admitted SAM patients were under 1 year of age and 24% were between 1 and 2 years. Most of the patients have rural residences nearly 93%, as most of the vicinity of our institute belonged to rural areas. According to Modified Kuppuswamy’s socio-economic status (SES) 46% that is maximally belonged to the Lower middle class and 45% belonged to the Lower class of SES. Out of 100 children, 20% were having magnesium deficiency and 56% children were having phosphate deficiency. Conclusion: Survival of children was significantly associated with random blood sugar, mg, and PO4 level. Therefore, timely identification and intervention of biochemical derangement in SAM patients are necessary to improve the survival of SAM patients.